PEMBATALAN AKTA NOTARIS: MEKANISME DAN PENYEBABNYA - Keumala, Dinda (Lex Jurnalica, 2024)
AbstractA Notary Deed is an authentic deed made by or before a Notary at the request of interested parties to be stated in the deed. In practice, the parties who have made the Notary deed want the Notary deed that has been made to be canceled for various reasons. The problem in this study is what is the mechanism for canceling notary deeds and what is the cause of the cancellation of notary deeds. This study uses a normative research type with the nature of descriptive research. Secondary data collection is carried out by literature methods and qualitative data analysis. The process of concluding is carried out by the deductive method. The results obtained from this study are that the mechanism for canceling the deed can be carried out by making a deed of cancellation in front of a Notary or filing a lawsuit for cancellation of the deed in the District Court. The cause of the cancellation of the Notary deed can be based on the agreement of the parties, one of the parties is in default, does not comply with the procedure for making a Notary Deed by the Notary Position Law and its amendments, the Notary is not authorized to do the deed, the substance of the deed is not by the applicable legal provisions, the deed is formally defective and the deed made is detrimental to one of the parties in the deed.Keywords: Annulment, Deed, Notary AbstrakAkta Notaris adalah akta otentik yang dibuat oleh atau dihadapan Notaris atas permintaan para pihak yang berkepentingan untuk dinyatakan dalam suatu akta. Dalam prakteknya, para pihak yang telah membuat akta Notaris menghendaki agar akta Notaris yang telah dibuat dibatalkan dengan berbagai macam alasan. Permasalahan dalam penelitian ini adalah bagaimanakah mekanisme pembatalan akta notaris dan apakah yang menjadi penyebab dibatalkannya akta notaris. Penelitian ini menggunakan tipe penelitian normatif dengan sifat penelitian deskriptif. Pengumpulan data sekunder dilakukan dengan metode kepustakaan dan analisis data menggunakan analisis kualitatif. Metode penarikan kesimpulan dilakukan dengan metode deduktif. Hasil yang diperoleh dari penelitian ini bahwa mekanisme pembatalan akta dapat dilakukan dengan membuat akta pembatalan dihadapan Notaris atau mengajukan gugatan pembatalan akta di Pengadilan Negeri. Penyebab dibatalkannya akta Notaris bisa berdasarkan kesepakatan para pihak, salah satu pihak wanprestasi, tidak memenuhi prosedur pembuatan Akta Notaris sesuai dengan Undang-undang Jabatan Notaris dan perubahannya, Notaris tidak berwenang untuk membuat akta, substansi akta tidak sesuai dengan ketentuan hukum yang berlaku, aktanya cacat formil dan akta yang dibuat merugikan salah satu pihak dalam akta tersebut.Kata kunci : Pembatalan, Akta, Notaris